Thr Ludruk Aesthetic Experience: East Java’ Traditional Humor - Misnal Munir, Moses Glorino Rumambo Pandin, Sumartono, (Opción, 2019)
The aim of the study is to find out the experience based on the artist and the spectators who enjoyed the ludruk humor in the perspective of aesthetic experience. The research method uses qualitative research with a library and field study approach. The findings shows that aesthetic experience kidungan humor ludruk reflect not only identity but also reflect the values that form aesthetic experiences inattention, intentional, coherent and complexity of the expression. In conclusion, the aesthetic experience of the audience in Kidungan Ludruk is formed through exposure and intentional exposure to the content coherence of the complexities of life.